Who limits environmental federalism in Croatia? - Dubravka Jurlina Alibegoviæ; Željka Kordej De Villa (European Regional Science Association (ERSA), 2004)
This paper explores the role of different levels of government in the design, implementation and enforcement of environmental regulatory measures, including environmental financing mechanisms. The first section presents basic theoretical insights of fiscal federalism. Further, it reviews factors which most affect the decision regarding the governmental level to be responsible for environmental protection – externalities, information, costs, interjurisdictional competition, and government capabilities. The second section elaborates the institutional and administrative framework of environmental policy and questions why local authorities are reluctant to take a more active role in shaping and financing environmental policy. One «success story» of local initiative in Croatia is described. Additionally, this section presents some evidence on budget revenues related to environmental protection and natural resource management, both at central and local levels. The last section summarizes our analysis and offers several recommendations aiming at the improvement of environmental policy.
Keywords: 330